Long-run comparisons of spending per pupil across different stages of education - Chris Belfield; Claire Crawford; Luke Sibieta (Institute for Fiscal Studies (IFS), 2017)
Education spending is the second-largest area of public service spending in the UK, representing about 4.5% of national income in 2015-16. Government spending on education grew by around 1.7% per year in real terms over the 1980s and 1990s, before increasing sharply over the 2000s by more than 5% per year in real terms. With the exception of 16-18 education spending, most areas of education have been protected from cuts since 2010-11. We have created measures of spending per pupil in England across the four main stages of education stretching back to the early 1990s for the first time. These series of day-to-day spending per pupil allow us to understand how policy changes have affected resources available to students in different stages of education over the long run (...)
Keywords: 330